Thioflavin T in-gel staining for ex vivo analysis of cardiac amyloid - Oldam, Joseph; Tchernyshyov, Irina; Van Eyk, Jennifer; Troncoso, Juan; Glabe, Charles G.; Agnetti, Giulio (Frontiers in Molecular Biosciences, 2025)
There are limited options to quantify and characterize amyloid species from biological samples in a simple manner. Thioflavin T (ThT) has been used for decades to stain amyloid fibrils, but to our knowledge, we were the first to use it in-gel. Thioflavin T in-gel staining is convenient as it is fast, inexpensive, accessible to most laboratories, and compatible with other fluorescent stains and downstream analyses such as mass spectrometry (MS).